Interoception in individuals with autism spectrum disorder: a systematic literature review and meta-analysis - Klein, Marlene; Witthöft, Michael; Jungmann, Stefanie Maria (Frontiers in Psychiatry, 2025)
This systematic review and meta-analysis synthesize current research on interoception in individuals with autism spectrum disorder (ASD) across the lifespan. A total of 31 studies meeting stringent inclusion and quality criteria were identified, incorporating both descriptive and numerical analyses of cardiac interoceptive accuracy (cIA), interoceptive sensibility (IS), and interoceptive awareness (IAW) in children, adolescents, and adults with ASD. The meta-analysis of five adult studies using comparable assessment tools found no significant differences in cIA between adults with ASD and neurotypically developed (NTD) controls [N = 5; μ^ = −.21 (SE = .11), p = .06]. Descriptive summaries of studies in children and adolescents, as well as those examining IS and IAW across age groups, revealed inconsistent findings—some studies reported reduced, increased, or similar interoceptive abilities in ASD compared to NTD. Methodological diversity, differences in measurement instruments, and variability in sample characteristics likely contribute to these inconsistencies. Moderator variables such as age, intelligence quotient (IQ), and comorbidities may influence interoceptive outcomes. Overall, the evidence indicates that ASD is not systematically associated with altered cIA, and the relationship between ASD and other interoceptive dimensions remains unclear. These findings underscore the need for more standardized methodologies and longitudinal research to clarify developmental trajectories and potential clinical implications of interoceptive processing in ASD. A deeper understanding of these mechanisms could lead interventions aimed at improving emotion regulation and social functioning in ASD.Systematic review registrationhttps://osf.io/f3ru4, identifier [doi.org/10.17605/OSF.IO/F3RU4].